Verticalization in the city of Santos (SP): impacts on urban sustainability and quality of life - Simões, Kelly Araújo; Tavares, Marcelo da Silva; Teixeira, Sabrina Aparecida Costa; Tourinho, Andréa de Oliveira; Sígolo, Letícia Moreira (Technical and Scientific Journal Green Cities, 2024)
Santos (SP), currently the most verticalized city in Brazil and with one of the most permissive urban legislations in the country, presents an urban dynamic committed to maximizing real estate gains and the constitution of a territory marked by profound socio-spatial inequalities. Verticalization, an ongoing phenomenon that promotes the multiplication of urban space, increasingly present in small and medium-sized Brazilian cities, is part of the strategies adopted by proponents of verticalization and has caused significant social, economic, and environmental impacts in the region. The purpose of this paper is to analyze the socio-environmental impacts arising from the verticalization process - encouraged by public policies -, as challenges to promoting sustainability associated to the quality of life of the citizens of Santos. Some of the impacts addressed include the capacity of existing drainage infrastructure, shading, microclimate alteration, waste generation, mobility, and socio-spatial segregation, based on primary data extracted from the certificate of occupation since 2012, as well as analyses of population commuting times, among others. These studies result of an ongoing postgraduate research group in architecture and urbanism, which, since 2023, has focused on the impacts of verticalization in the city of Santos. The urban unsustainability of this process is clear, requiring public policies committed to social and environmental justice to reverse this situation, ensuring that verticalization benefits the entire population in a more equitable manner.